Assessment of Knowledge, Attitude and Practice of Community Pharmacist towards the Provision of Pharmaceutical Care: A Community Based Study - Inamdar, Syed Zia; P, Apsy; J, Rosy; R.V, Kulkarni; K, Gazala; H, Kavaya; A, Bhuneshvari; H, Sapna (Indian Journal of Pharmacy Practice)
Background: The concept of pharmaceutical care was introduced in developed countries about three decades ago. Pharmaceutical care is the responsible provision of drug therapy for the purpose of achieving definite outcome which improve patient quality of life. Objective: To assess the Knowledge Attitude and Practice of community pharmacist in the deliverance of pharmaceutical care at community pharmacy level. Methodology: A survey study was conducted among various community dwelling pharmacies of Vijaypur city by administrating structured questionnaire to the working pharmacist to assess knowledge, attitude and practice in delivering pharmaceutical care. Result and Discussion: A total of 150 community pharmacies were surveyed in the study and hundred percent response rates was attained. There was a deficient knowledge (66.66%) with respect to pharmaceutical care and pharmacists are reluctant in accepting the responsibility of addressing patient drug related needs owing to knowledge gap and just restricting themselves to traditional drug dispensing practices. The attitude component; 62.69% community pharmacist are of the opinion that practicing pharmaceutical care is resource intensive that is time consuming, requires more man power. On Practice (70%) component; community pharmacist yearn to practice but they are deficient of adequate knowledge, attitude, resources and economics. Conclusion: There is deficit in knowledge and competence to practice pharmaceutical care among community pharmacist in the deliverance of Pharmaceutical health care.
Keywords: Pharmaceutical care; Knowledge; Attitude; Practice; Community pharmacist.